Pengaruh Bauran Pemasaran Jasa "House of Balloon" terhadap Niat Beli Ulang Konsumen - Paulus Rachmat Chayana (Jurnal Manajemen Maranatha, 2014)
The human needs change such as celebrate birthday party, business promotion, or memorable wedding. House of Balloon as a business in service of making shape balloon must improve their competitiveness, which is about the service marketing mix. A good implementation of service marketing mix canincrease the customer repurchase intention.This research objective is to determine the effect of service marketing mix to customer repurchase intention both partiallyand simultaneously. The data collection method using questionnaire survey for entire population and obtained the number of samples about 120 respondents whoever used the service of shape balloon House of Balloon. The research method using multiple regression analysis, t-test, F-test, and the coefficient determination.Based on the results, the calculated F value (18.065) larger than F table (2.09) and the significance level of 0.000 smaller than 0.05, which means the service marketing mix HOB affect the customer repurchase intention simultaneously. Based on result of t-test that only service marketing mix product (2.833), promotion (3.541), andprocess (3.374) that significantly affect the customer repurchase intention partially. The result of coefficient determination show that 50.1% customer repurchase intention influenced by the service marketing mix of HOB, while the rest influenced by other factors.Keywords: e-commerce, e-service, quality of service and buying interest.